INSOLVENCY OF AN ENTERPRISE AND METHODS OF FINANCIAL ANALYSIS FOR PREDICTING IT - Mackevicius, Jonas; Sneidere, Ruta (Ekonomika, 2010)
The purpose of this article is to draw attention to the topical problem of entity-level insolvency and the insolvency prediction models. Definitions, symptoms, causes and factors affecting insolvency, suggested by various authors, are reviewed. The impact of enterprise insolvency on a country’s economic growth is weighed up. Finally, the article presents the authors’ research work in the field of testing various enterprise insolvency forecast models and a system of insolvency prediction methods. Recommendations of possible solutions, based on the conclusion drawn from the research, are put forward.